Inhibition of human prostate smooth muscle contraction by the LIM kinase inhibitors, SR7826 and LIMKi3. (29th April 2018) - Yu, Qingfeng; Gratzke, Christian; Wang, Yiming; Herlemann, Annika; Sterr, Christian Maximilian; Rutz, Beata; Ciotkowska, Anna; Wang, Xiaolong; Strittmatter, Frank; Stief, Christian G; Hennenberg, Martin
Abstract : Background and Purpose: In men with benign prostatic hyperplasia, increased smooth muscle tone in the prostate may lead to bladder outlet obstruction and subsequent lower urinary tract symptoms. Consequently, medical treatment aims to inhibit prostate smooth muscle contraction. However, the efficacy of the treatment options available is limited, and improved understanding of mechanisms of prostate smooth muscle contraction and identification of new targets for medical intervention are mandatory. Several studies suggest that LIM kinases (LIMKs) promote smooth muscle contraction; however, this has not yet been examined. Here, we studied effects of the LIMK inhibitors on prostate smooth muscle contraction. Experimental Approach: Human prostate tissues were obtained from radical prostatectomy. Phosphorylation of cofilin, a LIMK substrate, was examined using a phospho‐specific antibody. Smooth muscle contractions were studied in organ bath experiments. Key Results: Real‐time PCR, Western blot and immunofluorescence suggested LIMKs are expressed in smooth muscle cells of prostate tissues. Two different LIMK inhibitors, SR7826 (1 μM) and LIMKi3 (1 μM), inhibited contractions of prostate strips, which were induced by electrical field stimulation, α1 ‐adrenoceptor agonists phenylephrine and methoxamine and the TXA2 analogue, U46619. LIMK inhibition in prostate tissues and cultured stromal cells (WPMY‐1) was confirmed by cofilin phosphorylation, which was reduced by SR7826 and LIMKi3. In WPMY‐1 cells, SR7826 and LIMKi3 caused breakdown of actin filaments and reduced viability. Conclusions and Implications: Smooth muscle tone in the hyperplastic human prostate may underlie the effects of LIMKs, which promote contraction. Contraction of prostate strips can be inhibited by small molecule LIMK inhibitors.